Management of hyper-flexion injury-related teardrop fracture in an adolescent - Maharaj, Monish (BMJ Case Rep, 2016)
We present a case of a flexion teardrop fracture managed surgically with anterior stabilisation and fusion between the affected vertebral body to its posteriorly adjacent level. A 14-year-old girl presented with severe neck pain following a fall from a bunk bed. MRI investigation showed signs of axial loading and hyper-flexion yielding a teardrop fracture at the body of the C5 vertebra. Using a novel technique, the patient was treated surgically with an anterior fusion of the C5-C6 vertebra. Her 12-month follow-up demonstrated full functional ability.